A progenitor binary and an ejected mass donor remnant of faint type Ia supernovae - Geier, S.; Marsh, T. R.; Wang, Bo; Dunlap, B.; Barlow, B. N.; Schaffenroth, Veronika; Chen, X.; Irrgang, Andreas; Maxted, P. F. L.; Ziegerer, Eva; Kupfer, Thomas; Miszalski, B.; et al. (Astronomy & Astrophysics, 2013)
Type Ia supernovae (SN Ia) are the most important standard candles for measuring the expansion history of the universe. The thermonuclear explosion of a white dwarf can explain their observed properties, but neither the progenitor systems nor any stellar remnants have been conclusively identified. Underluminous SN Ia have been proposed to originate from a so-called double-detonation of a white dwarf. After a critical amount of helium is deposited on the surface through accretion from a close companion, the helium is ignited causing a detonation wave that triggers the explosion of the white dwarf itself. We have discovered both shallow transits and eclipses in the tight binary system CD-30° 11223 composed of a carbon/oxygen white dwarf and a hot helium star, allowing us to determine its component masses and fundamental parameters. In the future the system will transfer mass from the helium star to the white dwarf. Modelling this process we find that the detonation in the accreted helium layer is sufficiently strong to trigger the explosion of the core. The helium star will then be ejected at such high velocity that it will escape the Galaxy. The predicted properties of this remnant are an excellent match to the so-called hypervelocity star US 708, a hot, helium-rich star moving at more than 750 km s-1, sufficient for it to leave the Galaxy. The identification of both progenitor and remnant provides a consistent picture of the formation and evolution of underluminous SNIa. © 2013 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Subdwarfs; Supernovae: general